Optimization of Agrobacterium tumefaciens-Mediated Transformation Systems in Tea Plant (Camellia sinensis) - Qianru LV; Changsong CHEN; Yijuan XU; Shunkai HU; Le WANG; Kang SUN; Xuan CHEN; Xinghui LI (Horticultural Plant Journal, 2017)
In this study, an efficient plant regeneration protocol in vitro and transformation by Agrobacterium-mediated method of Camellia sinensis was achieved, which would lay the foundation for genetic improvement of tea plant by genetic engineering technology. The cotyledon callus of C. sinensis were used as the receptors for transformation by Agrobacterium tumefaciens EHA105 containing PS1aG-3. Some factors which affected the result of Agrobacterium-mediated transformation of C. sinensis were studied on the basis of GUS transient expression system. The optimum system of Agrobacterium-mediated transformation was that the cotyledon callus were pre-cultured for 3 d, and then infected by EHA105 for 15 min followed by 3 d co-culture in the dark on the YEB medium containing 150 µmol⋅L−1 acetosyringone (AS). The transient expression rate of GUS gene was 62.6%. After being delayed selective culture for 3 d, infected callus were transferred into the differentiation medium and the root induction medium both of which were supplemented with 100 mg⋅L−1 spectinomycin, and then resistant seedlings of C. sinensis were obtained. The conversion rate was 3.6%.